Vinamilk: Fruit juice for kids in Vietnam - DIMIAN, Adel Fawzi (Institutional Knowledge at Singapore Management University, 2012)
The case starts as brand manager Mr Nguyen Trong Tan, sets out to launch a new line of fruit juice for children in Vietnam. Vinamilk, the largest diary company in Vietnam, had identified this as a potential market and was interested in launching the new line under their minor fruit juice product line. The company, while relatively new to the juice market, saw this as a huge growth market and indeed a key to its future success. Unlike other developed markets, the Vietnamese market was unique in that it did not have a juice meant specifically for children and Mar. Nguyen was expected to capitalize on this by launching the new line in February of 2012. The task was far from easy as Mr Nguyen was faced with competition from several companies doing business in Vietnam, including international giants Coca-Cola (Minute Maid) and PepsiCo (Tropicana Twister) along with local companies such as Tan Hiep Phat Beverage Group (No. 1 Juice). He would also need to contend with high inflation in a market place that was more likely to make fresh juice at home than buy a ready to drink product from Vinamilk. Casting additional pressure on the launch was that his growth targets for all juice sales were nearly 100% for each the next two years. The case starts as Mr Nguyen begins the challenge of creating a new product in a tough market.